Difuryl(supermesityl)borane: a versatile building block for extended π-conjugated materials12. Issue 31 (31st May 2018) - Riensch, Nicolas A.; Fritze, Lars; Schindler, Tobias; Kremer, Marius; Helten, Holger
Abstract : B-Doping of oligo(hetarene)s led to very robust, air-stable π-conjugated materials that are strong electron-acceptors and blue light emitters. Abstract : Direct functionalization and Pd-catalyzed cross-coupling of difuryl(supermesityl)borane (1 ) led to highly emissive organoborane compounds3 and4 . Photophysical and TD-DFT studies reveal an increase of the HOMO levels with higher hetarene content and stabilization of the HOMO and LUMO levels through B-doping, leading to very robust, air-stable electron-accepting materials.